Pengujian White Box Basis Path Testing Fitur Menghitung Aplikasi ComfyLearn - Michelle Valene Tanod; Husni Angriani; Afifah (STMIK KHARISMA Makassar, 2026)
This research aims to test the learning features in the ComfyLearn application using the white box testing method with the basis path technique. ComfyLearn is an Android-based educational application aimed at young children in learning while playing. To ensure the quality and reliability of applications, systematic software testing is required. This research applies the white box testing method with the basis path testing technique to test the program code for the learning counting feature, because this method is able to evaluate the program logic as a whole. This technique includes making flowcharts, flowgraphs, graph matrices, calculating cyclomatic complexity, determining independent paths, and preparing test cases. Based on the calculation results, it shows that the counting feature has a cyclomatic complexity value of 5, including the low category. This means that the complexity of the program logic is not too high so there is relatively little potential for errors to be found. There are 5 independent paths that need to be tested. Testing is carried out through unit testing and manual testing to verify whether the learning process has run as expected. The test results show that the program code in the learning counting feature functions well and meets expectations after making improvements. Thus, it can be concluded that the code structure in this feature section is quite reliable and can be used as a basis for further development.